Post-exercise Os Supranaviculare and Tenosynovitis in Young Adult Females (Revista de Medicina Clinica, 2022)
Clinical Snapshot presented in issue 6 number 1 of january of 2022 in Journal of Clinical Research
Keywords: Os Supranaviculare; Tenosinovitis